Efecto de fosfolípidos y antioxidantes en crioconservantes sobre la calidad seminal post-descongelación en bovinos en el cantón Morona - Ramos Ludeña, Luis Alberto (2025)
The cryopreservation of bovine semen is a key tool to ensure the conservation and use of high-value genetic material. The present study investigated the effects of phospholipids and antioxidants present in cryopreservatives on post-thaw semen quality in Charolais cattle. The research was conducted in the Morona canton, Morona Santiago province, where semen was collected from three previously selected breeders, all of which were evaluated as free from pests and diseases, and with adequate nutritional and body condition. Semen collection was performed using an artificial vagina from the brand Minitube, previously conditioned, and the semen material was collected in 15 mL Falcon tubes. The obtained samples were analyzed fresh to assess their fertility, and then underwent the predilution process. They were conditioned at 37°C for 40 minutes, and the total dilution was calculated. Next, the formula was applied to determine the number of straws to be used, followed by the straw filling, sealing, and cooling to -4°C for 4 hours before beginning the freezing process. The straws were placed in a rack and underwent a gradual freezing process in a homemade cryopreservator (foam cooler), with three freezing levels set at 2, 6, and 8 cm, with varying exposure times at each level, before finally being immersed in liquid nitrogen. Post-thaw semen quality was assessed using the CASA (Computer-Assisted Semen Analysis) system, where variables such as sperm concentration and motility were analyzed. Statistical analysis was performed using a mixed model, where each animal acted as an experimental block and received both treatments. A mixed model was used in the analysis of variance, with treatment as a fixed effect and animals as a random effect. The results indicated that the cryopreservative containing phospholipids and antioxidants showed a significant improvement in total motility (67.5%) and progressive motility (55.1%) compared to the base cryopreservative, which showed values of 49.7% and 41.3%, respectively. In conclusion, the results obtained in this research demonstrated that treatment with cryopreservatives containing phospholipids and antioxidants showed significantly superior preservation of post-thaw semen quality compared to the control group in the evaluated variables.